(3cJGH GdbQHI Edi QH GdYGdejf HGdUdGI Ydi eMeO SjOGdeQSdjfs - (3CHh GdbGSe Nda Hf YHO Gdedc Hf HTchGds; (3QGTO Hf gGTe GdQSJGbj GdfYeGfjs
(3ChdgG (B:s
(3bGd GdTjN gPG cJGH eNJUQ ai aVd GdUdGI Ydi GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3bGd aZdHJfi YjfGi , aQCjJ QShd Gddg Udi Gddg Ydjg hSde ai Gdfhe abGd di jGYJHi EdMb aHTQg Cf Gddg bO ZaQ dg Je s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(242 / 5 (3b(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs